Censorship or the Limits of Representation in Terrence McNally’s Gay Theatre at the End of the 20th Century - Xavier Lemoine (Revue LISA)
This paper explores the controversy around two contemporary American plays by acclaimed playwright Terrence McNally, Lips Together, Teeth Apart (1991) and Corpus Christi (1998). By detailing the ways these two plays were attacked by politicians and conservative religious groups, it becomes apparent that censorship is still at the heart of American democracy as is manifested by the ferocious debates around free speech as a result of the conservative revolution. Attitudes to homophobia then appeared to be a litmus test for free speech. The reception of these plays also highlighted the inner mechanism of censorship as a productive discourse that entails the risk of suppressing the artistic distance that provides a dissenting voice and a necessary criticism of the human condition.